REPRODUCTIVE OUTCOMES AFTER ABDOMINAL MYOMECTOMY - Fatima, Yasmin; Amir, Mumtaz (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of reproductive outcomes after abdominal myomectomy in infertile women.Study Design: Case series.Place and Duration of Study: at Combined Military Hospital, Multan Pakistan, from Sep 2015 to Feb 2017.Methodology: This study included 60 women who underwent myomectomy to retain their capabilities of reproduction. Inclusion criteria were infertile women with uterine fibroids. Routine investigation was done to all patients like ultrasound and hysterosalpingogram before and after the procedure. The procedure of abdominal myomectomy was done under general anesthesia. All fibroids were enucleated and large blood vessels were tied. Vicryl no.1 was used to close the uterine defect. All patients were followed up for 3, 6 and 12 months interval and data was collected for conception, spontaneous conception, and conception with assisted reproductive technique, live birth and miscarriage.Results: In this study mean age was 27.33 ± 4.03 years, mean number of fibroid was 1.366 ± 0.48 and mean size of fibroid was 7.06 ± 1.64 cm. Twenty eight (46.7%) women had conceived after myomectomy, in which 92.9% had spontaneous conception and 7.1% by assisted reproductive technique.Conclusion: Abdominal myomectomy should be the standard treatment of infertile women with uterine fibroids if no other underline cause of infertility. Moreover, this study results also showed that younger patients might be benefited more in term of reproductive outcomes after abdominal myomectomy.